The Social Construction of Knowledge in Learning: A Theoretical Review and Its Implications for Education - Ichsan, Rozaq Shohibul; Rofiq, Mohammad (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article aims to analyze the social construction of knowledge in the context of learning through a theoretical review of three main frameworks: (1) social constructivist theory in education, (2) the theory of social construction by Peter L. Berger and Thomas Luckmann in the sociology of knowledge, and (3) the concept of framing in media and communication. The research method employed is a systematic literature review with a philosophical–analytical approach. The analysis shows that knowledge in education is not an objective entity that is simply transferred, but rather the result of active construction through social interaction, language, and the dialectic of externalization, objectivation, and internalization. The social constructivist approach to learning aligns with Berger and Luckmann’s theory of social construction, in which pedagogical reality is jointly constructed by teachers and students within a socio-cultural environment. The concept of framing provides a lens for understanding how educational discourse is constructed and influenced by particular interests. The implications for education include the need for a paradigm shift toward learning that is more collaborative, reflective, critical, and sensitive to socio-cultural contexts. This article concludes that integrating these three perspectives can enrich understanding and promote more transformative educational practices that are relevant to the dynamics of contemporary society.